Velocidad de infiltración del agua empleando tres infiltrómetros en la finca experimental a maría - cantón Mocache - Ortiz Pico, Joffre Germán (2022)
vii The infiltration of water into the soil is a fundamental property that intervenes in important aspects such as its present and subsequent availability for crops, the recharge of underground aquifers or the geographical conformation of the territory. In the country there have been no investigations to determine the infiltration rate of water by means of infiltrometer rings, reason for which this investigation is proposed with the purpose of determining the permeability of the water and detecting the potential danger of erosion due to floods and runoff.